2012
DOI: 10.5539/ass.v8n13p172
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Program and Its Association with Job Satisfaction

Abstract: This article conceptually discussed recreational program, job satisfaction, and the relationship between both of them, the importance of recreational program and leisure satisfaction. Hence, it is essential to the organization to ensure; "does the recreational program contribute to job satisfaction?", "Does the recreational program could achieve organizational objectives?" and "what will be the contributions of running these programs?" The discussion indicates that recreational programs are known in a wide var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Job satisfaction is becoming a key factor in improving employees' working environments [1] [2] stated that researchers have demonstrated that job satisfaction improves absenteeism and organizational productivity. Ascertaining employee satisfaction is important for the performance of the employees of the organization [2]. Employee Satisfaction creates a more productive workforce in the organization that can reduce absenteeism [1].…”
Section: Background Of This Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Job satisfaction is becoming a key factor in improving employees' working environments [1] [2] stated that researchers have demonstrated that job satisfaction improves absenteeism and organizational productivity. Ascertaining employee satisfaction is important for the performance of the employees of the organization [2]. Employee Satisfaction creates a more productive workforce in the organization that can reduce absenteeism [1].…”
Section: Background Of This Studymentioning
confidence: 99%
“…Many employees do not participate in wellness programs. Wellness programs can increase operational costs for management and lessen the chances for effectiveness within the organization [2]. Wellness programs are gaining popularity among organizations' leaders [2].…”
Section: Background Of This Studymentioning
confidence: 99%
See 3 more Smart Citations